Selection of Outstanding Lecturers with Simple Additive Weighting Method - Wati, Embun Fajar; Istikharoh, Istikharoh; Tuslaela, Tuslaela (Politeknik Ganesha Medan, 2020)
Lecturers who excel have the right to be selected and get promotions and awards according to their academic performance. However, Sriwijaya State Buddhist College in Tangerang still uses manual assessment so it requires a lot of time to process the assessment data. Therefore, we need a method of calculation of SAW (Simple Additive Weighting) that can be used as a media for performance appraisal of outstanding lecturers who can facilitate an objective assessment. The SAW calculation aims to assist in the calculation of several criteria in the assessment of the right achieving lecturer. This assessment includes performance appraisals that include commitment, integrity, service orientation, discipline, cooperation, and leadership. In addition to the criteria, the assessment also includes the Employee Performance Target (SKP) assessment. The Employee Performance Target is in the form of a total assessment of lecturer performance. Two criteria, namely performance and SKP will be used as a guide in calculating the selection of outstanding lecturers. Samples were taken as many as 20 lecturers at Sriwijaya State Buddhist College in Tangerang. The simple additive weighting method is effectively used in the selection of outstanding lecturers with an assessment limit of more than 0.88. Of the many candidates, there are three lecturers with adequate performance and SKP, with grades 0.922, 0.88, 0.94. So that the highest achieving lecturer with the highest score is 0.94